Processing and characterization of waste leather based polycaprolactone biocomposites - Joseph, Seena; Ambone, Tushar S.; Salvekar, Abhijit V.; Jaisankar, S. N.; Saravanan, P.; Deenadayalan, E. (Polymer Composites, 2017)
Waste leather buff (WLB) filled polycaprolactone (PCL) composites were prepared by twin-screw extrusion varying the WLB content from 2% to 40%. These composites were extensively characterized by several techniques in order to establish micro and macroscopic properties. Addition of WLB resulted in improvement of tensile modulus of neat PCL and reduction in percentage crystallinity of PCL matrix was observed with increase in WLB content. Interfacial adhesion and dispersion of WLB on PCL matrix was investigated using Scanning Electron Microscope. Percentage of water uptake increased with increase in concentration of WLB in the composite. These biodegradable composites could be used to develop low cost materials suitable for applications in footwear industry, for making bags, suitcases, etc., eliminating the environmental issues arising from WLB generated from tanneries in leather industry. POLYM. COMPOS., 38:2889-2897, 2017. (c) 2015 Society of Plastics Engineers